Transformasi Evaluasi Pembelajaran Sastra melalui Gamifikasi: Implementasi Aplikasi Blooket pada Materi Hikayat di Kelas X Sekolah Menengah Atas - Nasution, Novi Safira Dani; Kartika, Rika; Soraya, Ratna (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
This study explores the development, validation, feasibility, and effectiveness of an evaluation tool assisted by the Blooket application for teaching fairy tale texts in Grade X of Sekolah Menengah Atas. Conducted at Sekolah Menengah Atas Negeri 13 Medan, the research employed a Research and Development (R&D) approach using the ADDIE model, encompassing the stages of Analysis, Design, Development, Implementation, and Evaluation. The study involved 427 students, with a purposive sampling technique used to select a sample of 35 students. Both qualitative and quantitative data were collected. The developed evaluation tool integrates gamification through the Blooket platform. Validation results from material experts reached 92% and 85% from Validators I and II, respectively, while design expert validations scored 91% and 87%. These results confirm the tool's high feasibility and effectiveness. In trials conducted with Class X-12, teacher satisfaction reached 94%, and student responses—based on questionnaires—were 92%, categorized as “Very Effective.” These findings affirm that the Blooket-assisted evaluation tool significantly enhances student engagement and comprehension. In conclusion, the developed tool is highly effective and suitable for implementing evaluation in literature learning, particularly in teaching narrative texts like fairy tales.